THE VALIDITY OF GENERAL BIOLOGY LEARNING EQUIPMENT BASED ON CASE METHOD AND PROJECT BASED LEARNING - Handayani, Dina; Restuati, Martina; Pratiwi, Nanda; Haniyyah, Ummu; Gultom, Rahmad H; Sanimah, Sanimah (Universitas Negeri Medan, 2024)
This research is a type of development research. The development method applied follows the define, design, and development Model. The aim of this study is to produce a valid general biology learning equipment based on case method and project based learning. In this research, the completed general biology learning equipment design was validated by content experts and language experts. Based on the validation results from content experts, the tool achieved a validation percentage of 86.65%, categorized as highly valid. The language experts validated the equipment with a percentage of 81.25%, also categorized as highly valid. Therefore, it can be concluded that the developed general biology learning equipment is suitable for testing by instructors of general biology courses.